Hispanic worker attitudes toward pig euthanasia on U.S. farms - Acevedo León, Nancy F.; Jaramillo, Pablo Lamino; Gabela, Carlos Durán; Boren-Alpízar, Amy; Andrukonis, Allison; Schmidt, Marcelo; McGlone, John; Garcia, Arlene (Frontiers in Veterinary Science, 2024)
On-farm pig euthanasia considers aspects of animal welfare and industry economics. Guidelines are available about the euthanasia process, but the agricultural workforce is highly diverse and guidelines do not consider cultural barriers. Euthanasia requires the ability to identify compromised pigs, technical skills, and willingness to euthanize pigs. The United States (U.S.) swine industry employs a high percentage of Latin American workers, some U.S. residents/citizens, and others through non-immigrant North American Free Trade Agreement (NAFTA) visas. These workers vary in their level of education and swine industry experience. Proper training of this workforce and identification of the barriers associated with performing timely euthanasia are critical to promote improved welfare practices. The objectives of this study were to: 1) develop a survey instrument to identify Hispanic caretaker attitudes toward pig euthanasia, 2) assess and describe swine caretakers' attitudes toward pig euthanasia using the developed survey instrument, and 3) determine the demographic and psychological barriers associated with performing pig euthanasia. Participants (n = 163) were surveyed from 16 farms across the state of Iowa. The results for demographics and the swine management survey data indicated that employees with less time working on the farm showed less knowledge of the CSIA, lower perceived ability to identify compromised pigs/pigs that needed to be euthanized, lower willingness to perform euthanasia on their own, and preferred not to have the responsibility of telling others when to euthanize pigs (p < 0.001). Secondary traumatic stress and transgressions were significantly correlated scales, associated to burnout, betrayals, and worker satisfaction (p = 0.022). Further, individuals identifying as female had higher secondary traumatic stress scores (p = 0.026) and lower compassion satisfaction scores (p = 0.015). This data suggests that there are demographic, psychometric, and training-related factors correlated with Hispanic caretakers' feelings about pig euthanasia. The results of this study could be used to further improve and develop targeted training programs for Hispanic caretakers for early identification of compromised pigs and timely euthanasia, which could benefit human well-being, and animal welfare, and the swine industry audit performance.